The Reciprocal Relationship Between Artificial Intelligence Adoption and Brand Equity: An Empirical Study in Türkiye (Third Sector Social Economic Review, 2025)
In today’s increasingly digitalized business environment, the adoption of Artificial Intelligence (AI) technologies has become a strategic component of internal brand management. The purpose of this study is to examine the effect of AI Adoption (AIA) on Employee-Based Brand Equity (EBBE) based on employee perceptions and to evaluate the reciprocal relationship between these two constructs. The research was conducted using a quantitative approach with a causal (relational) survey design. Data were collected through an online questionnaire from 398 employees working in organizations in Türkiye that actively utilize AI technologies, selected through convenience sampling. In the data collection instrument, a customer-based brand equity scale developed in Türkiye was adapted for employees, and the validity of this adaptation was tested through preliminary analysis and pilot testing. The factor structure was examined using IBM SPSS for Windows v.22, followed by structural equation modeling using IBM SPSS AMOS v.24 to validate and test the proposed model. The findings indicate that AIA significantly and positively influences EBBE, and EBBE similarly exerts a significant and positive effect on AIA, revealing a bidirectional relationship between the constructs. These effects are interpreted through the Resource-Based View and Dynamic Capabilities Theory for AIA, and Organizational Identity Theory and Social Exchange Theory for EBBE. Overall, the results highlight the critical role of AI technologies in enhancing employee-based brand value and strengthening competitive advantage.
Keywords: Artifical Intelligance (AI); AI Adaptation; Resource Based View; Competetive Advantage